Pengaruh Model Problem Based Learning dengan Pendekatan STEM Terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP Katolik Anda Luri: Penelitian - Marselia Hari; Mayun Erawati Nggaba (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the impact of implementing a Problem-Based Learning (PBL) model integrated with a STEM approach on students’ mathematical problem-solving abilities, specifically in the topic of probability, at Anda Luri Catholic Junior High School. The research employed a quantitative approach with a quasi-experimental design, utilizing a nonequivalent control group structure. The participants consisted of two groups: Class VIII A, serving as the control group and receiving conventional instruction, and Class VIII B, designated as the experimental group and instructed using the PBL model with a STEM approach. An essay-based assessment was administered as both a pretest and posttest to evaluate students’ problem-solving skills. The findings revealed a 55% improvement in the experimental group and a 38% improvement in the control group. Results from the independent samples t-test indicated a statistically significant difference, with a p-value of 0.001 (p < 0.05), thereby rejecting the null hypothesis (H₀) and supporting the alternative hypothesis (H₁). These results confirm that the integration of the PBL model with a STEM approach significantly enhances students’ mathematical problem-solving abilities.